RELATIONSHIP OF GESTATION AGE AND WEIGHT IN PREMATURE BIRTH WITH RETINOPATHY OF PREMATURITY IN A TERTIER HOSPITAL: Oral Presentation - Observational Study - Ophthalmologist - ABDI ROY NABABAN; Rozalina Loebis MD; Reni Prastyani MD (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Retinopathy of Prematurity (ROP) is the leading cause of preventable blindness in these children and significantly impacts vision. It is estimated that from about 15 million infants born prematurely worldwide, around 53,000 infants are found to have vision-threatening ROP, and 20,000 infants experience severe visual impairment. This study is to determine the relationship between gestational age and body weight in preterm birth with retinopathy of prematurity. Methods : Medical records data with a diagnosis of retinopathy of prematurity were found in 385 infants treated at Dr. Soetomo Hospital from January 2016-December 2020. From 385 premature infants, 45 premature infants were found with ROP. The relevant data is then entered into the recording sheet and Microsoft Excel software and processed using SPSS 22.0 software. Results : Premature infants with ROP who were found 385 infants with 45 infants were found with ROP. Premature infants with ROP in the gestational age group >32 weeks were 10 infants (22.2%). Of 45 premature infants, 23 premature infants with birth weights less than 1500 grams. AP ROP there is also 1 infant in the weight category Conclusion : There is a relationship between gestational age at premature birth and retinopathy of prematurity. Meanwhile, birth weight was not associated with retinopathy of prematurity. In infants with a gestational age of more than 32 weeks, it is still necessary for ROP because there is still a possibility of ROP.